1979
DOI: 10.5636/jgg.31.459
|View full text |Cite
|
Sign up to set email alerts
|

Some comparisons among geomagnetic field models, observatory data and airborne magnetometer data: Implications for broad scale anomaly studies over Canada.

Abstract: The secular change characteristics of several geomagnetic field models have been compared with the observed secular changes at sixteen magnetic observatories in Canada and nearby regions, for the period 1960 to the present. The significance of inadequacies in the secular terms of the field models when used as reference fields for the compilation of large scale magnetic surveys is discussed. Errors of the order of 50 nT/year are encountered with some models. A model derived primarily from satellite data shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The effect is small, but is important for long-wavelength studies, and the corrections have been applied to the data used in the subsequent analyses. COLES (1979) showed that the mean residual relative to POGO 6/71 for the combined surveys, after adjustment, was -12 T, with an r. m. s. deviation of 143 nT.…”
Section: Adjusting Surveys To a Common Epochmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect is small, but is important for long-wavelength studies, and the corrections have been applied to the data used in the subsequent analyses. COLES (1979) showed that the mean residual relative to POGO 6/71 for the combined surveys, after adjustment, was -12 T, with an r. m. s. deviation of 143 nT.…”
Section: Adjusting Surveys To a Common Epochmentioning
confidence: 99%
“…COLES (1979) has shown that inadequacies in the secular terms of the field models are sufficient to account for many, if not all, of these discrepancies. These effects are small enough that they do nott significantly affect the maps shown in Figs.…”
Section: Adjusting Surveys To a Common Epochmentioning
confidence: 99%
See 3 more Smart Citations